Investigation of biomolecular interactions using microelectrode arrays - Liu, Evangeline Jialin. (2011)
Over the past few years, there have been sudden outbreaks of new diseases such as SARS in 2003, which came as a surprise to everyone. Since viruses spread very rapidly, thus, fast and early detection of these new virus strands is therefore crucial.